Effect of the concentration of essential oil on orange peel waste biomethanization: Preliminary batch results. (February 2016) - Calabrò, P.S.; Pontoni, L.; Porqueddu, I.; Greco, R.; Pirozzi, F.; Malpei, F.
Highlights: We analysed the possibility of using orange peel waste for anaerobic digestion. Orange peel waste use is limited by the toxicity of orange essential oil. BMP tests were carried out at increasingly high concentrations of essential oil. Up to 370 N mL CH4 /g VS in mesophilic conditions were produced. A pathway for the biodegradation ofd -limonene to p -cymene was proposed. Abstract: The cultivation of orange ( Citrus × sinensis ) and its transformation is a major industry in many countries in the world, it leads to the production of about 25–30 Mt of orange peel waste (OPW) per year. Until now many options have been proposed for the management of OPW but although they are technically feasible, in many cases their economic/environmental sustainability is questionable. This paper analyse at lab scale the possibility of using OPW as a substrate for anaerobic digestion. Specific objectives are testing the possible codigestion with municipal biowaste, verifying the effect on methane production of increasingly high concentration of orange essential oil (EO, that is well known to have antioxidant properties that can slower or either inhibit biomass activity) and obtaining information on the behaviour ofd -limonene, the main EO component, during anaerobic digestion. The results indicate that OPW can produce up to about 370 Ln CH4 /kg VS in mesophilic conditions and up to about 300 Ln CH4 /kg VS in thermophilic conditions. The presence of increasingly high concentrations of EO temporary inhibits methanogenesis, but according to the results of batch tests, methane production restarts whiled -limonene is partially degraded through a pathway that requires its conversion into p -cymene as the main intermediate.